The European crisis and the transformation of transnational governance : authoritarian managerialism versus democratic governance - Glinski, Carola; Joerges, Christian (Hart Publishing, 2014)
"The debate on law, governance and constitutionalism beyond the state is confronted with new challenges. In the EU, confidence in democratic transnational governance has been shaken by the authoritarian and unsocial practices of crisis management. The ambition of this book, which builds upon many years of close co-operation between its contributors, is to promote a viable interdisciplinary alternative to these developments. "Conflicts-law constitutionalism" is a concept of transnational governance which derives democratic legitimacy from the supranational control of the external impact of national decision-making, on the one hand, and the co-operative responses to problem interdependencies on the other. The first section of the book contrasts Europe's new modes of economic governance crisis management with the conditionality of international investments, and reflects upon the communalities and differences between emergency Europe and global exceptionalism. Subsequent sections substantiate the problma̦tique of executive and technocratic rule, explore conflict constellations of prime importance in the fields of environmental and labour law, and discuss the impact and limits of liberalisation strategies. Throughout the book, European and transnational developments are compared and evaluated."--Bloomsbury Publishing.